EFL TEACHERS’ MOTIVATION AND COMPETENCE IN AN INDONESIAN CONTEXT AS ASSESSED WITHIN THE FRAMEWORK OF MASLOW’S AND HERBERG’S THEORIES - Tambunan, Anna Riana Suryanti; Hamied, Fuad Abdul; Sundayana, Wachyu (Indonesian Journal of Applied Linguistics, 2018)
Using regression and descriptive analyses, this research was carried out to measure the nature of teachers? motivation as indicated by their job commitment and satisfaction, which was then used to predict the EFL teachers? competence. The participants were 42 high school English teachers from both public and private schools in Binjai, North Sumatera Province. Likert-type inventory on teachers? motivation, with items focused on job commitment and job satisfaction, and a fact-based, multiple choice assessment of teaching competences were employed. It was found that motivation as indicated by both teachers? commitment and satisfaction could have a significant impact on their competence. For the success of any school in achieving its predetermined goals, committed and satisfied human resources are therefore considered as the most critical assets. Thus, fostering commitment and satisfaction among teachers is essential because teachers, who are highly committed and satisfied, would tend to stay longer, perform better, and are actively involved in classroom, school and social activities.